Предмет: Математика,
автор: Fadeev98
2(3*-6x)-4(-2x-4)=-7
Ответы
Автор ответа:
0
2(3*(-6х))-4(-2х-4)=-7
2(-18х)+8х+16=-7
-36х+8х+16=-7
-28х=-23
х=-23/-28
х=0,82
2(-18х)+8х+16=-7
-36х+8х+16=-7
-28х=-23
х=-23/-28
х=0,82
Автор ответа:
0
2(3-6х)-4(-2-4)=-7
6-12х+8+16=-7
-12х=-6-8-16-7
-12х=-37
х=3,5
6-12х+8+16=-7
-12х=-6-8-16-7
-12х=-37
х=3,5
Похожие вопросы
Предмет: Алгебра,
автор: Meskail
Предмет: Алгебра,
автор: muracv
Предмет: Английский язык,
автор: rofu303
Предмет: Математика,
автор: даня050405
Предмет: Математика,
автор: slavakoltyshev